2016
DOI: 10.1177/1744806916646785
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin attenuates neuropathic pain induced by L5-VRT via the calcineurin/IL-10 pathway

Abstract: Previous studies have shown that ulinastatin, an effective inhibitor of the inflammatory response in clinical applications, can attenuate hyperalgesia in rodents. However, the underlying mechanism remains unclear. In the present study, we first examined the change in the calcineurin level, which plays an important role in regulating cytokine release in the nervous system, following lumbar 5 ventral root transection in the rat. Furthermore, we determined whether intraperitoneal (i.p.) injection of ulinastatin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Conversely, IL-10 was regarded as a powerful anti-inflammatory cytokine which exerted its anti-inflammatory effects in neuropathic pain. Such as repeated intrathecal injections of IL-10 could reverse mechanical hypersensitivity induced by neuropathic pain,40 IL-10 obviously reduced the inflammatory response via suppressing pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) at the site of nerve injury, IL-10 protein expression in DRG was significantly down-regulated in lumbar ventral root transection and CCI-induced neuropathic pain 41,42. Consistently, our present data revealed that SNI distinctly induced the up-regulation of IL-1β and IL-6 protein expression in the DRG, and along with the significant down-regulation of IL-10 level, which suggested that the imbalance between pro-inflammatory cytokines IL-1β, IL-6 and anti-inflammatory cytokine IL-10 in DRG contributed to SNI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IL-10 was regarded as a powerful anti-inflammatory cytokine which exerted its anti-inflammatory effects in neuropathic pain. Such as repeated intrathecal injections of IL-10 could reverse mechanical hypersensitivity induced by neuropathic pain,40 IL-10 obviously reduced the inflammatory response via suppressing pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) at the site of nerve injury, IL-10 protein expression in DRG was significantly down-regulated in lumbar ventral root transection and CCI-induced neuropathic pain 41,42. Consistently, our present data revealed that SNI distinctly induced the up-regulation of IL-1β and IL-6 protein expression in the DRG, and along with the significant down-regulation of IL-10 level, which suggested that the imbalance between pro-inflammatory cytokines IL-1β, IL-6 and anti-inflammatory cytokine IL-10 in DRG contributed to SNI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of exogenous IL-10 alleviates allodynia in animal models of CCI and paclitaxel-induced neuropathic pain [94,95]. Drugs such as calcineurin, uliastatin, plasmid DNA, and viral vector indirectly increase IL-10 concentrations [7,96,97], and may be promising therapeutic targets in the treatment of neuropathic pain.…”
Section: Targeting Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…It is mostly present in neurons expressing isolectin B4, calcitonin gene-related peptide, and neurofilament-200. Calcineurin is weakly expressed in glial fibrillary acidic protein-positive satellite cells in the DRG (Ouyang and others 2016). At the subcellular level, about half of calcineurin is cytosolic, and the other half is associated with the plasma membrane.…”
Section: Expression and Structure Of Calcineurinmentioning
confidence: 99%